2010
DOI: 10.5194/acp-10-2063-2010
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and origin of organic groups detected in boreal forest using an aerosol mass spectrometer

Abstract: Abstract. An Aerodyne quadrupole aerosol mass spectrometer (Q-AMS) was deployed in Hyytiälä, a forested rural measurement site in southern Finland, during a 2-week measurement campaign in spring 2005. Q-AMS measures mass concentrations of non-refractory species including sulphate, nitrate, ammonium and organics from submicron particles. A positive matrix factorization method was used in identifying two oxygenated organic aerosol (OOA) groups from the measured total organic mass. The properties of these groups … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
86
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 68 publications
26
86
3
Order By: Relevance
“…Here we conduct a study of the hygroscopicity of the organic component at supersaturated conditions, focusing on the oxygenated component under the assumption that the unoxygenated component is non-hygroscopic. Similar results have been published for subsaturated conditions (McFiggans et al, 2005;Raatikainen et al, 2010) and more recently for laboratory and ambient measurements ), although laboratory experiments have shown that organic aerosol hygroscopicity under subsaturated conditions can be lower than under supersaturated conditions (Petters et al, 2009b;Prenni et al, 2007;Wex et al, 2009). This study builds on the results from previous closure studies conducted in our group at urban and rural sites (Broekhuizen et al, 2006;Chang et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
“…Here we conduct a study of the hygroscopicity of the organic component at supersaturated conditions, focusing on the oxygenated component under the assumption that the unoxygenated component is non-hygroscopic. Similar results have been published for subsaturated conditions (McFiggans et al, 2005;Raatikainen et al, 2010) and more recently for laboratory and ambient measurements ), although laboratory experiments have shown that organic aerosol hygroscopicity under subsaturated conditions can be lower than under supersaturated conditions (Petters et al, 2009b;Prenni et al, 2007;Wex et al, 2009). This study builds on the results from previous closure studies conducted in our group at urban and rural sites (Broekhuizen et al, 2006;Chang et al, 2007).…”
Section: Introductionsupporting
confidence: 83%
“…The presence of fresh SOA in these particles is not surprising since the fast particle growth rate leaves little time for oxidative aging. The high contribution of carbonaceous matter to aerosol growth is consistent with previous measurements of aerosol composition with AMS in Hyytiälä (Allan et al, 2006;Raatikainen et al, 2010). Figure 3b shows particle compositions scaled to total growth rate for each of these events.…”
Section: Resultssupporting
confidence: 86%
“…As shown by Raatikainen et al (2010), the organic aerosol in Hyytiälä in spring/summer can be thought of as a mix of two oxidized organic aerosol constituents. Jimenez et al (2009) converted the estimated growth factors of the two constituents to κ values of 0.2 and 0.0, respectively.…”
Section: Comparison Of D Crit From the Ccn Concentration And Hygroscomentioning
confidence: 99%